Экономическое и техническое содействие СССР зарубежным странам - Греков Ю. Н. Юрий Николаевич; Качанов А. И. Александр Иванович; Сухопаров Д. И. Дмитрий Иванович; Теодорович Т. В. Тадеуш Владимирович; Качанов А. И. (Москва, Международные отношения, 1987)
Исключено из фонда НТБ ТПУ